PENGGUNAAN METODE TANYA JAWAB DALAM PEMBELAJARAN MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN DI SMA DHARMAWIRAWAN PEPABRI MAKASSAR - Asriadi, Muhammad; Masni, Masni (Lembaga Penelitian dan Pendidikan Mandala, 2021)
The Use of the Question and Answer Method in Learning Citizenship Education Subjects at Dharmawirawan Pepabri High School Makassar. This research was conducted at Dharmawirawan Pepabri High School Makassar. The purpose of this research is to (1) determine the application of the question and answer method by the subject teachers of Citizenship Education at Dharmawirawan Pepabri High School Makassar, (2) provide an overview of knowledge about teacher and student perceptions of the use of the question and answer method in the learning process at Citizenship Education subject at Dharmawirawan Pepabri High School Makassar, (3) to find out how the obstacles a teacher faces in applying the question and answer method at Dharmawirawan Pepabri High School Makassar. This study uses a qualitative descriptive approach, with data collection carried out through interview and documentation techniques. The sample in this study were 2 class XI teachers. The results showed that: (1) The application of the question and answer method in the learning process of civic education at the Dharmawirawan Pepabri High School Makassar was considered to be running well. This is evidenced by the results of interviews conducted with Citizenship Education teachers who show that the application of the question and answer method in the learning process is to facilitate interaction between teachers and students so that learning activities will be more effective and efficient.(2) The consideration of a teacher choosing the question and answer method at Dharmawirawan Pepabri High School Makassar, to apply the question and answer method, which is to give effect to students to always be ready to master the subject matter before starting the teaching and learning process at school so that students will always focus on the material provided. (3) The obstacles faced by a teacher in applying the question and answer method at the Dharmawirawan Pepabri Makassar High School are divided into (a) the student factor (b) the duration factor, (c) the facility factor.